Philosophy as Creativity - Tereschenko, Natalia Anatolievna (International Journal of Criminology and Sociology, 2022)
The main aim of the study is to analyze the phenomenon of creativity, which has traditionally been the subject of philosophical investigation. Moreover, the phenomenon of philosophy itself as a creative process often remained in the shadow of general problems. By tacit agreement the creative nature of philosophy was recognized as obvious, and therefore, as a subject of philosophizing, it was often simply left out of the picture. However, again and again, the thesis about the “death of philosophy” makes the question of its creative nature more than relevant. If the creative potential of philosophy has been exhausted, perhaps it is really dying as a special form of thought in culture. If creativity in philosophy is possible, then its cultural prospects become more optimistic, or cultural elimination of philosophy is associated not only (or not so much) with its creative capacity. Creativity became the object of theorization in the Renaissance and Modernity, when man was initially thought of as its subject. Therefore, the very understanding of creativity bears the mark of Modern thinking. However, the "post-" situation forces us to return to the analysis of the problem and consider it in terms of the impossibility of the new. The problem can and should also be considered on the material of Russian philosophical thought, whose status has always been ambiguous, primarily for Russian philosophy itself. Today, the position of Russian philosophy is becoming even more problematic due to the problematization of philosophy as a particular discourse that claims to be universal, on the one hand, and the specifics of Russian theoretical thought labeled as "responsive", its empathicity – on the other.